The Effect of Fertilization by Humic Acid and Foliar Spraying with Nano-Micro-Nutrients on the Productive Traits of Solanum melongena L. - Shehab, Ola Hussein; Ibrahim, Nagham Saddon (Journal for Research in Applied Sciences and Biotechnology, 2022)
A factorial experiment was carried out according to the design of the completely randomized sector (R.C.B.D.) in the greenhouse of one of the nurseries in Al-Khalis district, located in the north of Diyala governorate, about 55 km from the capital Baghdad, investigate the effect of humic acid, nano-zinc oxide and nano-iron oxide on vegetative growth characteristics for eggplant, the planting experiment was carried out in the autumn season, on 9/10/2021. The experiment included treating the eggplants with 50 kg. ha-1 of humic acid and 50 to 100 mg. 1 liter of zinc oxide nanoparticles ZnO and iron oxide nanoparticles Fe3O4. The study results showed significant differences at the probability level of 5% between the averages of all the studied traits due to treating plants with humic acid. The study's results also showed that the highest averages were obtained from the treatment with zinc oxide nanoparticles at a concentration of 50 mg. L-1. Significant differences were also obtained in the length of the fruit (cm), the yield of a plot of fruits (kg. plot-1), and the total yield (kg. hectare-1) as a result of treating the eggplant plant with nano iron oxide at a concentration of 50 mg. L-1.